2002
DOI: 10.1074/jbc.m202588200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Human Gene for Prostate Short-chain Dehydrogenase/Reductase (PSDR1) Encodes a Novel Retinal Reductase (RalR1)

Abstract: All-trans-retinoic acid is a metabolite of vitaminAll-trans-retinoic acid is a metabolite of vitamin A (all-transretinol) that functions as an activating ligand for a family of nuclear retinoic acid receptors (1). In target tissues, all-transretinoic acid is produced by the oxidation of all-trans-retinaldehyde catalyzed by cytosolic aldehyde dehydrogenases (Fig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 46 publications
2
73
1
Order By: Relevance
“…This study and others (3)(4)(5)7) showed that mRDH11 is expressed in ocular and extraocular tissues, suggesting multiple functions. A possible role of mRDH11 in intestinal absorption of ␤-carotene has been discussed (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study and others (3)(4)(5)7) showed that mRDH11 is expressed in ocular and extraocular tissues, suggesting multiple functions. A possible role of mRDH11 in intestinal absorption of ␤-carotene has been discussed (7).…”
Section: Discussionmentioning
confidence: 99%
“…The reverse reaction, oxidation of all-trans-retinol, is not catalyzed by mRDH11 (3). hRDH11 is able to catalyze this reaction, however, at a lower catalytic efficiency compared with all-trans-retinal reduction (5,7). In addition to retinaldehydes, mRDH11 catalyzes the reduction of short-chain aldehydes such as nonanal with K m ϭ 30 M (3).…”
mentioning
confidence: 99%
“…DHRS3 is a known retinoic acid-inducible gene (Cerignoli et al, 2002) that encodes a retinal reductase (Kedishvili et al, 2002). Retinol regeneration by DHRS3 depends on the presence of the cellular retinoic acid binding protein CRABP2 (Cerignoli et al, 2002), a gene that was concordantly upregulated in ATRA-treated Wilms tumor cells.…”
Section: Retinoid Signalingmentioning
confidence: 99%
“…However, because of the high concentrations of RBP2 in the intestine, it was suggested that the microsomal enzyme that utilizes retinal-RBP2 is likely a more physiologically relevant enzyme. From the literature, we have identified a microsomal retinal reductase RalR1 that is expressed in intestine and uses retinal in the presence of high concentrations of RBP1 [28]. However, the effects of RBP2, the major intracellular retinolbinding protein present in the intestine, on this enzyme had not been studied.…”
mentioning
confidence: 99%